Analisis Model Super â€œAâ€ pada Iklan Promosi Kampus di Televisi - Meliala, Robbikal Muntaha (Jurnal Studi Komunikasi, 2018)
One of private university or academy who persistent broadcasted their advertisement in television to attract desire of student candidate every year is Bina Sarana Informatika (BSI) Group. The advertisement had been broadcasted since 2009 until 2016 were packaged by different of story concept. But the appearance of advertisement from BSI Group STMIK Nusa Mandiri 2015 affected pro and contra in society especially netizen because it had been suspected ignore few regulations from Ethic of Indonesia Advertisement (EPI). This research aimed to know how message implementation of BSI Group advertisement in television toward desire of student candidates, include its production flow, how the message packaging to approach their audience target and its consequence in social aspect. Research methodology: Case Study. Conclusion: Advertisement of BSI Group STMIK Nusa Mandiri only fulfilled qualifications of Simple, Unexpected and Entertaining. But ignored categories of Persuasive, Relevant and Acceptable. Promotion message of BSI advertisement tend to humor form, offensive, popular language, were signed as strategy of marketing communication from BSI foundation to approach the audience class C. Quick Studying, Affordable Cost, and Quick to Work are three layers of hard selling promotion message from BSI Foundation which announced to the audiences.